2019
DOI: 10.1016/j.scitotenv.2018.10.287
|View full text |Cite
|
Sign up to set email alerts
|

Rusty river: Effects of tufa precipitation on sediment entrainment in the Estero Morales in the central Chilean Andes

Abstract: Rivers and streams continuously shape and reform their channels through the transport of sediment. One of the most important parameter used to assess this transformation is the threshold for incipient grain motion. To date, limited studies have reported that several biotic and abiotic factors can affect this parameter. However, the effects of tufa precipitation on sediment entrainment and dynamics are still unexplored. The Estero Morales is an Andean stream in Central Chile affected by the phenomenon of tufa p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 63 publications
0
2
0
1
Order By: Relevance
“…However, the reference value may slightly vary as conditions for incipient motion of sediment in rivers depend on a variety of physical factors, such as turbulence, grain size, slope, and relative submergence being commonly assessed as the most important ones (Bathurst et al., 1987; Lee & Balachandar, 2012). Indeed, several studies (e.g., Buffington & Montgomery, 1997; Bunte et al., 2013; Ravazzolo et al., 2019) reported values ranging from 0.03 to 0.06. In this study, we showed that sand addition exerts a substantial effect on sediment incipient motion.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reference value may slightly vary as conditions for incipient motion of sediment in rivers depend on a variety of physical factors, such as turbulence, grain size, slope, and relative submergence being commonly assessed as the most important ones (Bathurst et al., 1987; Lee & Balachandar, 2012). Indeed, several studies (e.g., Buffington & Montgomery, 1997; Bunte et al., 2013; Ravazzolo et al., 2019) reported values ranging from 0.03 to 0.06. In this study, we showed that sand addition exerts a substantial effect on sediment incipient motion.…”
Section: Discussionmentioning
confidence: 99%
“…Having specified the unique color characteristics of the karst lakes, we took the average of the water quality data measured at different layers of various sampling points as values for the lake. The calcite saturation index (SI C ) can be obtained via the earth chemical simulation software PHREEQC [56,57]. The equation is as follows:…”
Section: Discussionmentioning
confidence: 99%
“…Natrium karbonat biasanya terjadi secara alami di daerah (236) kering terutama endapan material (batuan evaporit) yang akan terbentuk ketika danau musiman mengalami penguapan. Endapan (92)(93)(94)(95)…”
Section: Pendahuluanunclassified